Facile and sensitive detection of influenza viruses using SERS antibody probes. Issue 87 (6th September 2016) - Moon, Jeong; Yi, So Yeon; Hwang, Ahreum; Eom, Gayoung; Sim, Jieun; Jeong, Jinyoung; Lim, Eun-Kyung; Chung, Bong Hyun; Kim, Bongsoo; Jung, Juyeon; Kang, Taejoon
Abstract : We report facile and sensitive influenza virus detection method using surface-enhanced Raman scattering antibody probes. Abstract : It is highly important to identify influenza viruses rapidly and accurately for the prevention of future pandemic outbreaks. We developed an easy and sensitive influenza virus detection method using surface-enhanced Raman scattering (SERS) antibody probes. The SERS antibody probes can be prepared easily by mixing Au nanoparticles, gold binding peptide-protein G, and antibodies without complicated chemical or biological reactions. They also retain the optimal conformation for the antibody's interaction with Influenza A/CA/07/2009 (pH1N1), allowing us to detect pH1N1 sensitively and selectively. This method provides a detection limit of 4.1 × 10 3 TCID per mL and is highly selective for pH1N1. We anticipate that this method can be useful in a wide range of immunoassays.